10‐year analysis of human immunodeficiency virus incidence in first‐time and repeat donors in Brazil. Issue 2 (30th September 2020) - de Oliveira Garcia Mateos, Sheila; Preiss, Liliana; Gonçalez, Thelma T.; Di Lorenzo Oliveira, Claudia; Grebe, Eduard; Di Germanio, Clara; Stone, Mars; Amorim Filho, Luiz; Carneiro Proietti, Anna Bárbara; Belisario, Andre Rolim; de Almeida‐Neto, Cesar; Mendrone‐Junior, Alfredo; et al.
Abstract : Background and objectives: Incidence in first‐time and repeat blood donors is an important measure of transfusion‐transmitted HIV infection (TT‐HIV) risk. This study assessed HIV incidence over time at four large blood centres in Brazil. Materials and methods: Donations were screened and confirmed using serological assays for HIV from 2007 to 2016, and additionally screened by nucleic acid testing from 2011 forward. Limiting antigen (LAg) avidity testing was conducted on HIV seroreactive samples from first‐time donors to classify whether an infection was recently acquired. We calculated incidence in first‐time donors using the mean duration of recent infection and in repeat donors using classical methods. Time and demographic trends were assessed using Poisson regression. Results: Over the 10‐year period, HIV incidence in first‐time donors was highest in Recife (45·1/100 000 person–years (10 5 py)) followed by São Paulo (32·2/10 5 py) and then Belo Horizonte (23·3/10 5 py), and in repeat donors was highest in Recife (33·2/10 5 py), Belo Horizonte (27·5/10 5 py) and São Paulo (17·0/10 5 py). Results from Rio de Janeiro were available from 2013 to 2016 with incidence in first‐time donors of 35·9/10 5 py and repeat donors from 2011 to 2016 of 29·2/10 5 py. Incidence varied by other donor demographics. When incidence was considered in 2‐year intervals, no significant trend was evident. Overall residual risk of TT‐HIV was 5·46 and 7·41 per million units of pRBC and FFP transfused, respectively. Conclusion: HIV incidence in both first‐time and repeat donors varied by region in Brazil. Clear secular trends were not evident.